Umeščanje Katoliške cerkve v ameriško družbo od ustanovitve apostolske prefekture Baltimore leta 1784 do prve svetovne vojne = Relation of the American Catholic Church to the Institutions of American Society from the Establishment of the Apostolic Prefecture of Baltimore in 1784 to the First World War - Herle, Dominik Janez (Edinost in dialog, 2022)
The article deals with the positioning of the Catholic Church in American society from the founding of the Apostolic Prefecture of Baltimore in 1784 to the First World War. The paper begins with a quote from Rudolph Veccoli, the longtime director of the Immigration History Research Center at the University of Minnesota, who wrote that the history of the Catholic Church in the United States is actually the history of the Catholic Church's relationship to immigrant communities. The authors also note that the contribution of the Slovenian higher clergy to the development of the structures of the Catholic Church in the USA was significant, especially in the area of Michigan's Upper Peninsula and Northern Minnesota, Iron Range. The contribution describes some of the important issues, i.e. the establishment of the institutions of the Catholic Church after the American Revolution and its placement in American society until the First World War; the attitude of the Catholic hierarchy in the USA and the role of the Roman Curia towards the Americanization of immigrants and/or the preservation of their ethnic identities; the development of Catholic education and the attitude of the Catholic Church in the USA towards the institutions of public education; the movement to Americanize the Catholic Church; its attitude to the issue of slavery and its attitude to the African-American community after the abolition of slavery, as well as the question of the attitude of the Catholic Church to the treatment of the Native Americans by the USA till the end of the 1st World War.